Citrus Yellow Vein Clearing Virus Infection in Lemon Influences Host Preference of the Citrus Whitefly by Affecting the Host Metabolite Composition - Yong-Duo Sun; Christopher M. Wallis; Rodrigo Krugner; Raymond Yokomi (Plants)
Plant viruses have been known to alter host metabolites that influence the attraction of insect vectors. Our study investigated whether Citrus yellow vein clearing virus (CYVCV) infection influences vector attractiveness, focusing on the citrus whitefly, Dialeurodes citri (Ashmead). Free choice assays showed that citrus whiteflies exhibited a preference for settling on CYVCV-infected lemon plants versus healthy control plants. Using chromatography techniques, we found that the levels of sugars were similar in leaves and stems of both plant groups, while the contents of several amino acids in leaf or stem samples and non-volatile phenolic compounds in the leaf samples of CYVCV-infected and healthy plants differ drastically. In addition, volatile terpenes/terpenoids decreased significantly in virus-infected plants compared to healthy controls. Several of the identified volatile compounds such as α-phellandrene, α-terpinolene, p-cymene, linalool, and citral are known for their whitefly repellent properties. Further Y-tube olfactometer bioassays revealed that emissions of volatile organic compounds (VOCs) from infected plants attracted more citrus whiteflies, but not alate spirea aphids, Aphis spiraecola Patch, than those from healthy plants, suggesting that the VOCs released from CYVCV-infected lemon plants may specifically affect citrus whiteflies. Therefore, we suggest that, in addition to the visual cue of yellow vein symptoms, the preference of citrus whiteflies that settled on CYVCV-infected lemon plants was attributed to a reduction in the levels of repellent volatile compounds.